Assistance On Packaging And Marketing Innovations In The Soy Milk Business - Robustin, Tri Palupi (IMPOWERMENT SOCIETY, 2021)
Soy milk owned by Mrs. Fida is a home industry business that has been established for quite a long time. Soy milk produced is pure soy milk without preservatives with the composition of soy, sugar, salt and food coloring. Soy milk is marketed only in traditional markets, namely in Karang Duren Market and the owner has not expanded his marketing area. The problem faced by this home industry is in the field of expanding its marketing area and packaging. Soy milk is only distributed in one traditional market so that the product is less well known in other areas. The packaging of soy milk products is also classified as still not good and quality, because the plastic wrap is thin and prone to tearing and sometimes not labeled with product-related information. Based on these problems, soy milk home industry owners need assistance to market their products to other regions in order to be known by the public. In addition to marketing assistance, this devotional activity also provides assistance related to more quality packaging. Based on this reason, this community service activity aims to help Mrs. Fida as the owner of soy milk home industry in marketing her products in other areas. Product marketing is done by selling to consumers who need soy milk products in the gym / fitness center, because soy milk is high in protein that is much needed by people who exercise. This community service activity also provides guidance on related knowledge to make packaging more attractive and quality and provide capital for Mrs. Fida.